SAT0330 Large Areas of Cartilage Damage and Full Thickness Cartilage Loss Increase Risk for Incident Radiographic Osteoarthritis. (23rd January 2014) - Roemer, F. W.; Guermazi, A.; Hannon, M. J.; Eckstein, F.; Hunter, D. J.; Boudreau, R.; Wang, Z.; Grago, J.; Kwoh, C. K.
Abstract : Background: Prevalent cartilage damage is one of the strongest risk factors for progression of further cartilage loss in knees with and without OA. It is likely that prevalent cartilage damage also increases risk of ROA, however it is unknown if area extent, % of full thickness loss or both play a role for the development of ROA. Objectives: The aim of the study was to assess if area extent of cartilage damage and % of full thickness cartilage loss one year prior to the occurrence of incident ROA (time point "P-1") and at study enrollment ("baseline") increase the risk for incident ROA in a nested, matched case-control study in the Osteoarthritis Initiative (OAI) cohort. Methods: Participants were drawn from the OAI including 4796 participants with, or at risk of knee osteoarthritis. We studied 105 knees that developed incident ROA before the 48 month visit. Knees were selected based on the following definition: either KL 0 in both knees or KL 0 in one knee and KL 1 in the contralateral knee at baseline. They were 1:1 matched with a control knee that did not develop incident ROA, with the same KL grade in both knees at baseline, and for gender and age within 5 years. MR images were acquired at four OAI clinical centers using Siemens Trio 3 T scanners. MRIs were read for cartilage damage in 14 articular subregions using the semiquantitative MOAKS system, reporting both the amount of area extent per subregion (from 0 to 3) and the percentage of subregion that is affected by full thickness cartilage loss (also from 0 to 3). Conditional logistic regression was used to assess the risk of incident ROA in regard to maximum grade for area for the medial and lateral compartments at P0 and baseline. In addition, the maximum grade of prevalent full thickness damage per knee was analyzed in regard to risk for ROA for the time point P-1 and baseline. Results: Subjects were on average 58.6 years old (SD ± 8.5), predominantly female (62.8%) and overweight (mean BMI 28.0 SD ± 4.7). Knees with any full thickness cartilage damage at P-1 showed an increased risk for ROA when compared to knees without full thickness damage (OR 1.93 95% CI [1.04, 3.61]). For baseline, knees with focal full thickness lesions (=grade 1) in areas of otherwise intact cartilage or in areas with prevalent superficial damage had and increased risk for ROA when compared with knees without full thickness damage as the reference (OR 2.57 95% CI [1.19, 5.50]). At P-1 risk of incident ROA was significantly increased for knees exhibiting prevalent cartilage damage with a maximum area grade of 2 or 3 in at least one subregion in the lateral compartment (odds ratio (OR) and 95% confidence intervals (CI) were 2.00 [1.05, 3.80] when compared to knees with only a maximum grade of 0 or 1. Conclusions: Presence of large areas of cartilage loss in at least one subregion in the lateral compartment predicted incident ROA one year later. Knees with any full thickness damage had an increased risk for ROA when compared to knees without full thickness damage. In regard to baseline, only knees with focal full thickness defects had an increased risk of ROA regardless of area extent. Disclosure of Interest: F. Roemer: None Declared, A. Guermazi Shareholder of: Boston Imaging Core Lab, LLC, Consultant for: Astra Zeneca, Genzyme, Novartis, Stryker, Merck Serono, M. Hannon: None Declared, F. Eckstein Shareholder of: Chondrometrics, D. Hunter Grant/research support from: Australia Research Council Future Fellowship, Consultant for: DonJoy, NIH, Stryker, R. Boudreau: None Declared, Z. Wang: None Declared, J. Grago: None Declared, C. K. Kwoh Consultant for: Novartis